Clinicopathological features and ethnic disparities of melanoma in the United Arab Emirates: 2017–2025 - Jonathan Mokhtar; Nada Alsuwaidi; Nada Hassane; Rose Mary Eapen; Hind Aljanaahi; Dalia AlDhamin; Tannaz Rahbari; Ghazal Talal Saeed; Zainab Abdulla Al Darwish; Sara Almalik; Jeyaseelan Lakshmanan; Tom Loney; et al. (PLoS ONE, 2026)
Background Cutaneous melanoma incidence is rising globally, yet clinicopathological data from the high ultraviolet (UV) environment in the United Arab Emirates (UAE), with its diverse expatriate population, remain scarce. This study aims to characterize the histopathological features of cutaneous melanoma in a large, multi-ethnic cohort in the UAE. Methods This retrospective cross-sectional study analyzed histopathologically confirmed cases of cutaneous melanoma diagnosed at a specialized dermatopathology laboratory in the UAE from 01/01/2017–01/01/2025. Patient demographics, tumor location, histologic subtype, Clark level, Breslow thickness, mitosis, lymphovascular, and perineural invasion were extracted and analyzed. Descriptive statistics, group comparisons, and multivariable logistic regression were performed using IBM SPSS version 29.0 to identify predictors of thick melanoma (Breslow thickness >1.0 mm). Results A total of 597 patients met the inclusion criteria (50.8% male; mean age 47.4 ± 12.3 years). Individuals of European ancestry constituted 73.4% of cases. Superficial spreading melanoma was the predominant subtype (58.5%), and 46.9% of melanomas were thin (≤1.0 mm). Males presented with significantly thicker tumors than females (Breslow thickness of 0.72 ± 1.32 vs. 0.50 ± 0.58 mm; p < 0.01) and exhibited distinct anatomical distributions predominant to the trunk as compared to females with leg predominance. Multivariable analysis confirmed nodular melanoma (OR 18.40; 95% CI [7.08, 47.86]; p < 0.001) as the single strongest independent predictor of thick melanoma. Conclusion Melanoma in the UAE disproportionately affects fair-skinned expatriates and frequently presents with sex-specific clinical patterns. These findings highlight the need for targeted public awareness initiatives to reduce melanoma morbidity and mortality in the region.